DEEP LEARNING FOR MEDICAL IMAGE ANALYSIS - ZHOU KEVIN S; HAYIT GREENSPAN; DINGGANG SHEN (CAMBRIDGE ELSEVIER INC ACADEMIC PRESS, 2024)
This book serves as both a textbook and reference for researchers, medical imaging specialists, and AI engineers. It systematically presents how deep learning methods, particularly convolutional neural networks (CNNs), autoencoders, recurrent networks, and generative adversarial networks (GANs), have transformed medical image analysis tasks such as detection, segmentation, classification, and diagnosis.
MEDICAL IMAGE ANALYSIS
COMPUTER SCIENCE
Keywords: MACHINE LEARNING; COMPUTER SCIENCE